DEVELOPMENT OF TEACHING MATERIALS WITH ELICITING ACTIVITIES MODELS BASED ON ETHNOMATHEMATICS TO IMPROVE MATHEMATICAL LITERACY ABILITY - Yohanes Jefrianus Kehi; Maria Naimnule (JURNAL EDUSCIENCE, 2023)
This research is a development research (R & D) which aims to produce a mathematics teaching material with ethnomathematics-based eliciting activities. The method used in this study is a development research method with five stages as follows: (1) Preliminary Investigation, (2) Design, (3) Realization/Construction, (4) Test -Evaluation and Revision (Test, Evaluation and Revision) and (5) Implementation (Implementation) but in this study, development was only carried out up to the first 4 stages because the implementation stage required a long process and time. The results of the validation of teaching materials and other tools by mathematicians and media experts show an average score of 4.46 which is classified as very good. and students, then a trial was carried out to see the effectiveness of learning through a mathematical literacy ability test where the results showed an average completeness of 80.25% in the good category. The conclusion of this study is that mathematics teaching materials using the eliciting activities model based on ethnomathematics are categorized as good and appropriate for use in teaching mathematics in junior high schools.Keywords: teaching materials, eliciting activities models, ethnomathematics, mathematical literacy skillsÂ Abstrak Penelitian ini merupakan penelitian pengembangan (R & D) yang bertujuan untuk menghasilkan suatu bahan ajar matematika dengan eliciting actvities berbasis etnomatematika. Metode yang digunakan dalam penelitian ini merupakan metode penelitian pengembangan dengan lima tahapan sebagai berikut: (1) investigasi awal (Preliminary Investigation), (2) Perancangan (Design), (3) Realisasi/Konstruksi (Realization/Construction), (4) Tes-Evaluasi dan Revisi (Test, Evaluation and Revision) dan (5) Implementasi (Implementation) namun Pada penelitian ini, pengembangan hanya dilakukan sampai pada 4 tahapan awal karena pada tahap implementasi memerlukan proses dan waktu yang cukup lama. Hasil validasi bahan ajar beserta perangkat lainnya oleh ahli matematika dan ahli media menunjukkan rata-rata skor 4,46 yang tergolong dalam kategori sangat baik, hasil uji coba kepraktisan bahan ajar dan perangkat lainnya menunjukkan bahwa semuanya dalam kategori praktis hal ini ditunjukkan melalui data aktivitas guru dan siswa, selanjutnya dilakukan uji coba untuk melihat keefektifan pembelajaran melalui tes kemampuan literasi matematika dimana hasil menunjukkan rata-rata ketuntasan 80,25% dengan kategori baik. Kesimpulan dari penelitian ini adalah bahan ajar matematika dengan model eliciting activities berbasis etnomatematika dikategorikan baik dan layak untuk digunakan dalam pembelajaran matematika di sekolah menengah pertama.Kata Kunci: Bahan Ajar, Model Eliciting Activities, Etnomatematika, Kemampuan Literasi Matematika